Plasma metabolite profiles, cellular cholesterol efflux, and non-traditional cardiovascular risk in patients with CKD. (November 2017) - Ganda, Anjali; Yvan-Charvet, Laurent; Zhang, Yuan; Lai, Eric J.; Regunathan-Shenk, Renu; Hussain, Farah N.; Avasare, Rupali; Chakraborty, Bibhas; Febus, Annie J.; Vernocchi, Linda; Lantigua, Rafael; Wang, Ying; et al.
Abstract: Background: Patients with chronic kidney disease (CKD) experience high rates of atherosclerotic cardiovascular disease and death that are not fully explained by traditional risk factors. In animal studies, defective cellular cholesterol efflux pathways which are mediated by the ATP binding cassette transporters ABCA1 and ABCG1 are associated with accelerated atherosclerosis. We hypothesized that cholesterol efflux in humans would vary in terms of cellular components, with potential implications for cardiovascular disease. Methods: We recruited 120 CKD patients (eGFR < 30 mL/min/1.73 m 2 ) and 120 control subjects (eGFR ≥ 60 mL/min/1.73 m 2 ) in order to measure cholesterol efflux using either patients' HDL and THP-1 macrophages or patients' monocytes and a flow cytometry based cholesterol efflux assay. We also measured cell-surface levels of the common β subunit of the IL-3/GM-CSF receptor (IL-3Rβ) which has been linked to defective cholesterol homeostasis and may promote monocytosis. In addition, we measured plasma inflammatory cytokines and plasma metabolite profiles. Results: There was a strong positive correlation between cell-surface IL-3Rβ levels and monocyte counts in CKD (P < 0.001). ABCA1 mRNA was reduced in CKD vs. control monocytes (P < 0.05), across various etiologies of CKD. Cholesterol efflux to apolipoprotein A1 was impaired in monocytes from CKD patients with diabetic nephropathy (P < 0.05), but we found no evidence for a circulating HDL-mediated defect in cholesterol efflux in CKD. Profiling of plasma metabolites showed that medium-chain acylcarnitines were both independently associated with lower levels of cholesterol transporter mRNA in CKD monocytes at baseline (P < 0.05), and with cardiovascular events in CKD patients after median 2.6 years of follow-up. Conclusions: Cholesterol efflux in humans varies in terms of cellular components. We report a cellular defect in ABCA1-mediated cholesterol efflux in monocytes from CKD patients with diabetic nephropathy. Unlike several traditional risk factors for atherosclerotic cardiovascular disease, plasma metabolites inversely associated with endogenous cholesterol transporters predicted cardiovascular events in CKD patients. (Funded by theNational Institute of Diabetes and Digestive and Kidney Diseases K23DK097288 and others.) Highlights: Cholesterol efflux in humans varies in terms of cellular components. We report a cellular defect in ABCA1-mediated cholesterol efflux in CKD patients. Plasma metabolites predicted cardiovascular events in CKD patients.